Letter to Jane Tolmach from Stanley E. Cohen - Stanley E. Cohen:::::: (1966)
A letter to Mrs. Jane Tolmach, Stanley E. Cohen explains his absence from a recent meeting and addresses concerns about fundraising for Mr. Schlei's campaign. He denies rumors that a professional campaigner raised $1,000 in the Ventura-Oxnard area, stating that less than $150 was collected despite significant efforts, which did not even cover expenses. Cohen notes that he personally advanced a considerable sum to support television coverage, expecting local funds to reimburse it, but those funds were never raised and he will bear the loss. He adds that Schlei Headquarters has been unable to provide promised contributions to the coordinating committee, as fundraising has been weak across multiple counties. Cohen concludes that he will continue seeking resources but is not optimistic about securing additional funds.